Efisiensi Perusahaan: Apakah Busyness Dewan Komisaris Berkontribusi? - zaitul, Zaitul; ilona, Desi; Maharani, Shinta Dea; Ethika , Ethika; Rifa, Dandes (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
The busyness of the board members has become a hot topic since this can positively and negatively impact corporate governance outcomes, such as company efficiency. However, a limited study investigates the role of supervisory board busyness and company efficiency using Indonesian data. Therefore, this study aims to determine the relationship between supervisory board busyness and company efficiency. In addition, this study also analyzes the effect of the supervisory board experience and size on firm efficiency. Forty-two publicly listed transportation companies are employed as research samples. Secondary data from the annual and financial reports are used, and multivariate regression analysis is applied. This study found that supervisory board experience is positively related to company efficiency (α=5%). Hence, the company's efficiency is achieved if the supervisory board has more experience. Besides, this study also found that company profitability, leverage, and size significantly related to company efficiency.